Where Do, I Lie? - O'Hara, Emily (Auckland University of Technology, 2012)
This research engages the creative practices of filmmaking, photography, spatial installation and performance. It culminates in a gallery installation of serial interlinking works that instantiate the question of identity in relation to naming via the image and text, time and space, movement and death. Further the work enquires implicitly through a question of spatial design not only via installation practice but also through concerns for set design and the spatiality of time both on and of what constitutes the event of performance. This research is concerned with naming and identity as related to the photographic image, written and spoken word. The research is critically framed through Roland Barthes’ writing in ‘Camera Lucida’ (1980). This text uncovers a relation between the subjects in photography that is essential to the framing of my practice. Barthes names three subjects in the photographic arc; Operator, Spectator and Spectrum. These terms work as an underlying principle in the manifestation of my practical work. Barthes’ text is also instrumental in my reading of death in the imaged identity. Walter Benjamin’s essay ‘On Language as Such and on the Language of Man’ (1996) provided a moment of revelation with respect to communication that has served as the basis for my examination of language. Benjamin’s text is an examination of the space between the divine and the human, and as such provides a site through which I trace my examination of the space between name and identity. It is also framed through Jacques Derrida’s notion of deconstruction. I seek to interrogate and re-imagine the photographic, filmic and performance based outcomes of my practical work in the manner that Derrida examines literary texts. This process uncovers, in the way of Derrida’s reading practice, a ‘keystone’ through which the works can be re-read. These frameworks provide the site in which I seek to uncover the relations between naming, identity, performance and death. This project also touches on how domestic space and gender stereotypes condition the way we behave as an aside to my core research questions. The act of naming the child is closely linked to expressions of domesticity and Gaston Bachelard’s ‘The Poetics of Space’ (1994) provides insight with regards to both identity and domestic space. Bachelard asks us to encounter spaces that we inhabit daily, spaces that have become ordinary, in a new way. His notion that the spaces we live in shape our memories is extended in my practice to include spaces created via performance. I aim to interrogate how the temporal space of performance can fold the space the ‘other’ inhabits back and forth through recollection. Name and gender are the first accepted indicators of identity according to institutionalized practices. I am haunted by the ideal woman, she who cooks, cleans, takes care of the children, she who always looks and smells immaculate and tantalising, she who puts herself last. I am interested in how images (photographs, film and memory) create in their making, a future tense that we must become (or are trapped into their becoming). Is it possible that in my name lies the answer to how my imaged identity has been created?
Keywords: Performance; Death; Identity; Naming; Film; Photography; Deconstruction